Getting started with the McData Intrepid FICON director - White, Bill (IBM, International Technical Support Organization, 2003)
This IBM Redbooks publication discusses how to install, tailor, and configure the McDATA Intrepid FICON Director, in conjunction with the FICON topologies supported by zSeries and 9672 Generation 5 and Generation 6 servers. It focuses on the hardware installation as well as the software definitions needed to provide connectivity for supported FICON environments. This book provides planning information and FICON Director setup information. Also included are helpful utilities for monitoring and managing the McDATA Intrepid FICON Director environment. This book is intended for system engineers, SAN administrators, and system programmers who will plan and install McDATA Intrepid FICON Directors. A good background in systems planning, hardware and cabling infrastructure planning, and zSeries I/O definitions (HCD or IOCP), as well as Fibre Channel or FICON Directors is assumed.
Includes bibliographical references (page 87) and index. - Print version record
Keywords: Fibre Channel (Standard); Computer input-output equipment; Storage area networks (Computer networks); Fibre Channel (Norme); Ordinateurs; Équipement d'entrée-sortie; Réseaux de stockage (Informatique)